Place cells and long-term potentiation in the hippocampus - Cobar, Luis Fernando (2017)
Place cells show location-specific firing patterns according to an animal’s position in an environment and are thought to contribute to the spatial representation required for self-navigation. Decades of study have extensively characterized the properties of place cells and suggested the involvement of long-term potentiation (LTP), a long-lasting synaptic strengthening, in place cell activity. Here, we review the basic characteristics of place cell activity and the findings that support the idea that LTP contributes to the formation, maintenance, and plasticity of place cell activity.